2017
DOI: 10.1002/chem.201703484
|View full text |Cite
|
Sign up to set email alerts
|

Structural Analysis of Uranyl Complexation by the EF‐Hand Motif of Calmodulin: Effect of Phosphorylation

Abstract: Better understanding of uranyl-protein interactions is a prerequisite to predict uranium chemical toxicity in cells. The EF-hand motif of the calmodulin site I is about thousand times more affine for uranyl than for calcium, and threonine phosphorylation increases the uranyl affinity by two orders of magnitude at pH 7. In this study, we confront X-ray absorption spectroscopy with Fourier transform infrared (FTIR) spectroscopy, time-resolved laser-induced fluorescence spectroscopy (TRLFS), and structural models… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
45
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(48 citation statements)
references
References 72 publications
3
45
0
Order By: Relevance
“…As shown by Berthomieu and co-workers [64], the phosphorylation of Thr at position 9 in the site 1 EF-hand motif of CaM, together with introduction of a Tyr at position 7, increased the binding affinity of uranyl by a factor of~5 (K D decreased from 25 to 5 nM) at pH 6, and by two orders of magnitude (K D = 0.25 nM) at pH 7. The direct involvement of phosphothreonine in uranyl coordination by a monodentate phosphoryl group was further confirmed by FTIR difference spectra and EXAFS data [66]. These observations suggest a crucial role for the phosphoryl group in enhancing the uranyl binding affinity of phosphorylated proteins at physiological pH.…”
Section: Binding To Native Metal-binding Sitesmentioning
confidence: 59%
“…As shown by Berthomieu and co-workers [64], the phosphorylation of Thr at position 9 in the site 1 EF-hand motif of CaM, together with introduction of a Tyr at position 7, increased the binding affinity of uranyl by a factor of~5 (K D decreased from 25 to 5 nM) at pH 6, and by two orders of magnitude (K D = 0.25 nM) at pH 7. The direct involvement of phosphothreonine in uranyl coordination by a monodentate phosphoryl group was further confirmed by FTIR difference spectra and EXAFS data [66]. These observations suggest a crucial role for the phosphoryl group in enhancing the uranyl binding affinity of phosphorylated proteins at physiological pH.…”
Section: Binding To Native Metal-binding Sitesmentioning
confidence: 59%
“…Phospho-T-CaM diminishes SK channel conductance [66]. HypertensionGQNP T 44 EAELAffect EF-hand II In vivo KMKD T 79 DSEEAffect flexible central linkerKDTD S 81 EEEIAffect flexible central linker In vitro Phospho-T 29 -CaM enhances uranium binding [75,76]. Cell toxicityNGYI S 101 AAELAffect EF-hand IIICaMK-IV In vitro Phospho-T 44 -CaM, phosphorylated by CaMK-IV, inhibits CaMK-II [68]GEKL T 117 DEEVAffect EF-hand IVPKCα In vitro Melatonin enhances phospho-S/T-CaM levels [72].…”
Section: Phospho-tyr-cam In Pathophysiologymentioning
confidence: 99%
“…Uranium chemical toxicity in living organisms is due, in part, to the interaction of the uranyl ion with cellular proteins. The first EF-hand Ca 2+ -binding motif of CaM has about thousand times more affinity for uranyl than for Ca 2+ , and in vitro studies demonstrated that phosphorylation of Arabidopsis thaliana CaM by CK2 at a threonine in the first Ca 2+ -binding loop, increases the uranyl affinity at physiological pH [75,76]. Another kinase known to phosphorylate the first EF-hand Ca 2+ -binding site of vertebrate CaM at Thr29, and in lesser extent Thr26, is MLCK [77].…”
Section: Phospho-ser/thr-cam In Pathophysiologymentioning
confidence: 99%
“…26 The highest affinity was achieved for peptide CaM-M1c (sequence in Scheme 1), which basically retains the sequence of the site I of native calmodulin (CaM-nat). The difference between CaM-M1c and CaM-nat are (1) Phe 13 and Val 29 substitutions by Cys with concomitant disulfide-bridge formation to keep the peptide in a folded state, (2) fluorescence labeling through Thr 20 Tyr mutation. Because the highest affinity was achieved for the peptide retaining its natural sequence, their attempts to engineer ''uranyl binder'' essentially failed.…”
Section: Uranyl(vi) Binding To Cyclic Peptidesmentioning
confidence: 99%